Social and economic impact of SEZs in India - Aggarwal, Aradhna (New Delhi ; Oxford : Oxford University Press, 2012)
This text provides a comprehensive review of the evolution and performance of SEZs in India from a historical and comparative perspective. Critically reviewing India's policy, it analyses the economic rationale of SEZs and their impact on employment trade, foreign exchange earnings, government revenue, and technology transfers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: India -- Economic policy -- 1991-; Economic development -- Social aspects -- India